2020
DOI: 10.21608/msnj.2020.188042
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Performance of Mothers Having Children with Cancer Undergoing Chemotherapy

Abstract: Background: Cancer is a leading cause of death for children worldwide. More than 80% of children with cancer are cured in high-income countries, but only 20% are cured in many low-income countries. Aim: To assess the knowledge and performance of mothers having children with cancer undergoing chemotherapy. Research design: Descriptive research design was used in the current study. Sample: A purposive sample of 35 mothers having children with cancer and undergoing chemotherapy participated in the study. Setting:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…More than two fifth of children were the second order in the Qur'an group and also, more than two fifth were the third order in the music group. The result of the current study contradicted with Hasan, Mohamed, Ahmed, Riad & Ali (2020) (57) who studied "Knowledge and Performance of Mothers Having Children with Cancer Undergoing Chemotherapy in EL mania" and found that the mean of age of mothers was 42.5 ± 5.4 years, more than half of them have basic education. And the study supported that all of mothers who participated in the study were mothers, and most of them lived in rural areas.…”
Section: Discussioncontrasting
confidence: 99%
“…More than two fifth of children were the second order in the Qur'an group and also, more than two fifth were the third order in the music group. The result of the current study contradicted with Hasan, Mohamed, Ahmed, Riad & Ali (2020) (57) who studied "Knowledge and Performance of Mothers Having Children with Cancer Undergoing Chemotherapy in EL mania" and found that the mean of age of mothers was 42.5 ± 5.4 years, more than half of them have basic education. And the study supported that all of mothers who participated in the study were mothers, and most of them lived in rural areas.…”
Section: Discussioncontrasting
confidence: 99%